COMPARING ANTIBACTERIAL POTENTIAL AND PHYTOCHEMICAL CONSTITUENTSOF TWO SPECIES OF GENUS URTICA: Pharmaceutical Science-Plant physiology and biochemistry - RAJPUT, PRIYANKA; CHOUDHARY, MAITRY; R.A. SHARMA (International Journal of Life Science and Pharma Research, 2019)
The present study was conducted to evaluate and compare the in-vitro bioactive potential of various organic extracts of the root, stem and leaves of Urtica dioica and Urtica urens on growth of tested Gram Positive (+ve) and Gram negative (–ve) bacteria.The present investigation also includes the comparative chemical constituency of the crude extract of root, stem and leaves of both plants. The comparative bioactive potential of Urtica dioica and Urtica urens was tested against both pathogenic and non-pathogenic strains of bacteria that are Gram positive (Staphylococcus aureus and Bacillus subtilis) and Gram negative (Pseudomonas aeruginosa and E. Coli) conducted by using agar well diffusion method .The Minimum Inhibitory Concentrations (MICs)-the lowest concentration of antimicrobial agent that will inhibit any visible growth of microbein chloroform and methanol extracts of root, stem and leaves of both plants was determined using micro-well dilution method. For the phytochemical evaluation of plants metabolites- ascorbic acid, flavonoids, phenols and proteins has been quantitatively estimated. The MIC has been to be most effective in case of methanolic extract of root against both gram positive and gram negative bacteria. Significant antimicrobial activity has been observed against gram negative bacteria E. coli and both the gram positive bacteria testedexpressed by U. dioica comparatively more effective than U. urens. Only a moderate amount of activity is exhibited against P. aeruginosa by both the plants. The non-polar extracts were found to have comparatively higher bactericidal potential than the polar extracts. The phytochemicals analysis suggested the presence of ascorbic acid, phenols and proteins to be found in U. urens in significantly higher concentration than U. dioica. On the other hand, U. dioica has been found to be more abundant in flavonoid concentration comparatively.